Tandem promoters determine regulation of the Klebsiella pneumoniae glutamine synthetase (glnA) gene. - Dixon, R (1984)
Transcription of the structural gene for glutamine synthetase (glnA) in Klebsiella pneumoniae is controlled by the nitrogen regulatory genes ntrA, ntrB and ntrC. The nucleotide sequence of the regulatory region upstream of the glnA gene is reported here. High resolution S1 mapping of in vivo transcripts indicates that the regulatory region contains tandem promoters separated by 100 nucleotides. Measurements of beta-galactosidase activities determined in vivo from glnA-lac fusions suggest that the upstream promoter (for RNA2) is negatively regulated by the ntrBC gene products whereas transcription from the downstream promoter (for RNA1) is positively activated by the ntrA gene product in the presence of either the ntrBC or the nifA genes. The nucleotide sequence of the upstream promoter resembles the consensus sequence for E. coli promoters, whereas the downstream promoter shows homology with the nitrogen fixation (nif) promoters of K. pneumoniae.